Makna Peran Gender bagi Suami Peserta Program Laki-Laki Peduli di Gunungkidul Daerah Istimewa Yogyakarta - Inggriani Leila Roosi; Wenty Marina Minza (Faculty of Psychology, Universitas Gadjah Mada, 2017)
The most Gunungkidul is a region that embraces the culture of Java and has a high number of domestic violence. Program Laki-Laki Peduli of Rifka Annisa Women Crises Center comes to Gunungkidul to encourage husbands in Gunungkidul to change their character identity to fit the positive masculinity. That means there is a conflict between the new men concepts with the concept that has been owned by them before (traditional concept of gender). This study will discuss that phenomenon. Through the qualitative method and phenomenological approach, this study involved two subjects who are alumni of Program Laki-Laki Peduli. This study aims to understand the psychological meaning of the subjects' gender role after experiencing the clash of two different gender role concepts. The data were collected through semi-structured interview with the subjects and data triangulation (subject and time) with the wives of the subjects. The results of this study showed that gender role of new men concept can emerge if subjects face the circumstances